2016
DOI: 10.1371/journal.pntd.0004962
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fasciola hepatica Infection with Liver Fibrosis, Cirrhosis, and Cancer: A Systematic Review

Abstract: BackgroundFascioliasis has been sporadically associated with chronic liver disease on previous studies. In order to describe the current evidence, we carried out a systematic review to assess the association between fascioliasis with liver fibrosis, cirrhosis and cancer.Methodology and Principal FindingsA systematic search of electronic databases (PubMed, LILACS, Scopus, Embase, Cochrane, and Scielo) was conducted from June to July 2015 and yielded 1,557 published studies. Among 21 studies that met inclusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 43 publications
2
56
0
5
Order By: Relevance
“…Diagnosis is currently performed through the use of high-sensitive serological and parasitological tools. Although most patients are asymptomatic, patients with acute infection normally present fever and abdominal pain, while patients with chronic infection present biliary colic, cholecystitis and cholangitis [4]. Conversely, there is a limited number of studies to evaluate the natural history of patients affected with fascioliasis to assert chronic inflammation, liver fibrosis stages and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is currently performed through the use of high-sensitive serological and parasitological tools. Although most patients are asymptomatic, patients with acute infection normally present fever and abdominal pain, while patients with chronic infection present biliary colic, cholecystitis and cholangitis [4]. Conversely, there is a limited number of studies to evaluate the natural history of patients affected with fascioliasis to assert chronic inflammation, liver fibrosis stages and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Like other helminths, F. hepatica infection and its excretory/secretory products (ESP) inhibit the development of M1 which facilitates the switch to the M2 phenotype, and modulates the host immune response by inducing potent polarized M2 (Th2) and by downregulating the production of M1 (Th1) macrophages [6,7]. Fascioliasis, which is caused by F. hepatica or F. gigantica afflicts at least 2.6 million people around the world [8,9], causes hepatic pathologies such as liver fibrosis, cirrhosis, and even cancer [10]. Moreover, fascioliasis outbreaks caused by F. gigantica in Yunnan, China further suggested that this pathogen might be zoonotic [11].…”
Section: Introductionmentioning
confidence: 99%
“…m/z 571) and as well as DNA-adducts (m/z 599) [4]. This was expected since these parasites all reside within the bile ducts and fascioliasis can induce DNA damage [10,17]. To reiterate, however, these were fewer of these compounds in F. hepatica compared to Opisthorchis spp.…”
Section: Resultsmentioning
confidence: 99%
“…results in comparable pathology in their definitive hosts including fibrosis, hyperplasia and biliary stasis [3,10,2123]. However, an association between fascioliasis and cancer remains controversial and not definitely established [10]. Thus, we decided to investigate extracts of adult worms of F. hepatica and compare with data previously obtained for Opisthorchis spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation